AB0452 Case report of allogeneic unrelated-donor mesenchymal stem cells (MSC) infusion in sjogren syndrome (SS) with refractory thrombocytopenia. (15th June 2017) - Qi, J; Qiu, M; Gu, J
Abstract : Background: Intravenous MSC infusion has been reported occasionally in SS treatmen and Immune Thrombocytopenia ttreament. To our knowledge, there is rare report of allogeneic unrelated-donor intravenous MSC infusion in SS with thrombocytopenia without immunosuppresive induction of MSC transplantation. Objectives: To report the case of a Sjogren syndrome with refractory thrombocytopenia treated with MSC infusion. To review the current literature on intravenous MSC infusion for SS. Methods: Literature review and multidisciplinary discussion were thoroughly performed before treatment protocol was approved by institutional ethics committee and patient and family signed informed consent form. Results: A 48 year-old female with a 2-year history of SS, manifested by severe thrombocytopenia (PLT 14–30*10E9/L, after each injection of recombinant human interleukin 11, platelets can be transiently recovered.) refractory to Methylprednisolone, methotrexate, azathioprine and cyclophosphamide received Four infusions (Once a month) of allogeneic unrelated-donor 2x10 6 /Kg MSC. After two infusiong of MSC, the PLT increased gradually to greater than 100*10E9/L. After 1 year of follow-up, Platelet counts remained normal. Conclusions: These results suggest that mesenchymal stem cells may be a therapeutic strategy for Sjogren syndrome with Refractory thrombocytopenia patients. Larger studies are needed to validate clinical efficacy and safety and to standardize treatment protocol of MSC infusion in SS. References: Zhang D, Li H, Ma L, et al. The defective bone marrow-derived mesenchymal stem cells in patients with chronic immune thrombocytopenia. Autoimmunity 2014, 47 (8), 519–29. Xu J, Wang D, Liu D, et al. Allogeneic mesenchymal stem cell treatment alleviates experimental and clinical Sjogren syndrome. Blood 2012, 120 (15), 3142–51. Wu M, Ge H, Li S, et al. Mesenchymal Stem Cells Immunosuppressed IL-22 in Patients with Immune Thrombocytopenia via Soluble Cellular Factors. Journal of immunology research 2015, 2015, 316351. Disclosure of Interest: None declared